RNA and microRNA Stability in PAXgene-Fixed Paraffin-Embedded Tissue Blocks After Seven Years' Storage. Issue 6 (5th April 2018) - Sanchez, Ignacio; Betsou, Fay; Culot, Bénédicte; Frasquilho, Sonia; McKay, Siobhan C; Pericleous, Stephanos; Smith, Colleen; Thomas, Gerry; Mathieson, William
Abstract: Objectives: To evaluate the stability of RNA and microRNA (miRNA) in PAXgene-fixed paraffin-embedded tissue blocks after 7 years' storage. Methods: RNA and miRNA were extracted from PAXgene-fixed paraffin-embedded (PFPE) blocks in 2009 then stored at −80°C. Seven years later, RNA and miRNA were again extracted from the same blocks. RNA and miRNA integrity in the 2009 and 2016 extractions were compared using RNA integrity number (RIN), paraffin-embedded RNA metric (PERM), reverse transcription polymerase chain reaction (RT-PCR) for different amplicon lengths, and quantitative RT-PCR (qRT-PCR) for three mRNA and three miRNA targets. Results: In PFPE blocks, mRNA was poorer in 2016 extractions compared to the 2009 extractions in all blocks and all assays applied, with transcripts degrading at different rates in the same blocks. For miRNA, qRT-PCR showed no statistically significant differences between 2009 and 2016 extractions. Conclusions: mRNA in PFPE tissue blocks degrades at room temperature storage over 7 years.